UJI KETAHANAN BEBERAPA VARIETAS JAGUNG TERHADAP PENYAKIT BULAI (PERONOSCLEROSPORA MAYDIS) DI RUMAH KACA - , RIKI RAMDANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Downy mildew is one of the important diseases on maize. In susceptible maize varieties it can caused 100% damage. The research aimed to determine the resistance of some maize varieties against downy mildew caused by Peronosclerospora maydis and determine the relation between density, length and width of stomata of maize plants with resistance to downy mildew. Research used completely randomized design (CRD) with 9 treatments and 5 replications. Varieties were Arjuna, Bisi 16, Bisi 816, BMD 35, BMD 36, BMD 37, BMD 38, Jagung Manis, and RD 09. The parameters measured were the disease incidence, stomata density, stomata length and width. Data were analyzed using ANOVA. The significant difference between varieties, was tested using DMRT at Î± 5%. Correlation and regression analysis were conducted to determine the relation between density, length, and width of stomata with disease incidence. The results showed a BMD 38 variety is resistant to downy mildew with disease incidence value of 2.47% and a RD 09 varietiy is susceptible to downy mildew with disease incidence value of 50.95%. Observations indicate that stomata density of Arjuna variety had the highest density of stomata and the stomata i.e, 126, while mean BMD 37 the lowest with 70 stomata. Arjuna have the longest average stomata 2.67 Âµm while RD 09 have the widest stomata i.e, 1.37 Âµm. Stomata density did not closely related to the downy mildew disease incidence and negatively correlated with the value of r = - 0.04. Stomata length had a fairly correlation to disease incidence of downy mildew but negatively correlated with the value of r = - 0.425. Stomata width had a closely correlation with the disease incidence of downy mildew and positively correlated with r = 0.604.